The CO2 Gas Absorption in Biogas Using Absorber Bubble Column with Variation of NaOH Absorbent Concentration and Sparger Forms - Purba, Elida; Rehmalem Barutu, Cecellia Nia (Universitas Negeri Semarang, 2021)
Biogas consists of CH4 50-70%, CO2 25-45%, and a small amount of H2, N2, and H2S. The quality of the biogas can be improved by removing the carbon dioxide content so that the gas can be used for fuel. This research discusses the biogas purification process using NaOH solution as the absorbent to determine the effect of the concentration of NaOH and the shape of the sparger on the CO2 absorption process in biogas using a bubble column. NaOH solution with a concentration of 2,75 M; 3 M; 3,25 M of 2 liters was inserted into the column with a diameter of 3 in. The biogas and absorbent are contacted in the opposite direction with a biogas flow rate of 1 liter/minute. Variations in the shape of the sparger used are the types of pipes and rings. Sample analysis was performed with Gas Chromatography 2014 AT (SHIMADZU corp 08128). From the research results, the higher the absorbent concentration the higher the percentage of CO2 absorption, but it is not known the best sparger design because of the difference in the number of holes and the length of the sparger. The most optimum percentage of CO2 absorption is 98.211% with a variation of the concentration of 3.25 M and a sparger with a pipe shape.